2004
DOI: 10.1007/s00256-004-0764-z
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal disorders associated with HIV infection and AIDS. Part I: Infectious musculoskeletal conditions

Abstract: The musculoskeletal system can be affected by a variety of abnormalities in association with human immunodeficiency virus (HIV) infection. Although not as common as complications involving other organ systems, such as the pulmonary and the central nervous systems, HIV-associated musculoskeletal disorders are sometimes the initial presentation of the viral illness. Knowledge of the existence and the characteristic appearance of the conditions affecting bone, joint, and muscle in HIV-infected patients is valuabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(34 citation statements)
references
References 77 publications
0
33
0
1
Order By: Relevance
“…Tuberculous pyomyositis is typically caused by invasion from adjacent structures rather than by primary infection, lymphatic spread, or hematogenous seeding [2]. The diagnosis of tuberculous pyomyositis is more common in immunodeficient patients and associated with the use of corticosteroids, the presence of HIV infection, the administration of cancer chemotherapy, and renal failure [2,6,10,14,16,20,24]. Tuberculous pyomyositis can develop in immunocompetent persons, with the common symptoms of evening rise of temperature, night sweats, malaise, loss of appetite, and weight loss [18].…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculous pyomyositis is typically caused by invasion from adjacent structures rather than by primary infection, lymphatic spread, or hematogenous seeding [2]. The diagnosis of tuberculous pyomyositis is more common in immunodeficient patients and associated with the use of corticosteroids, the presence of HIV infection, the administration of cancer chemotherapy, and renal failure [2,6,10,14,16,20,24]. Tuberculous pyomyositis can develop in immunocompetent persons, with the common symptoms of evening rise of temperature, night sweats, malaise, loss of appetite, and weight loss [18].…”
Section: Discussionmentioning
confidence: 99%
“…Bones, as well as joints or striated muscle [5][6][7][8] can be affected. Infections may affect peripheral joints, spine, long bones or muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculous infections may likewise involve soft tissue or bones/joints (Tehranzadeh et al, 2004). While it may be expected that HIV infection would lead to an increase in musculoskeletal infections, some studies have indicated that this may not be so (Bahebeck et al, 2004).…”
Section: Orthopedics 451 Musculoskeletal Infectionsmentioning
confidence: 99%